Sistem informasi Pengelolaan Proyek Berbasis website Menggunakan Metode Prototype - Hanik, Umi; Ni’mah, Asshyffatul Aina Ni’mah; Tandiyo Dwi Oktavia (LPPM STIMATA, 2024)
This research aims to design and implement a Web-based Project Management System for Bengkel Las Santoso, operating in Sumberjo Village, Blitar. Given the widespread development of information technology, this study includes an analysis of the existing manual data management system currently in use at Bengkel Las Santoso. The primary goal is to enhance the efficiency and effectiveness of data management by integrating information technology. The new system is designed to manage stock data, orders, transactions, customer and staff management, as well as generate daily and monthly reports. Additionally, this system will facilitate customers in obtaining information about their payment status and orders. This research is expected to provide an innovative solution for Bengkel Las Santoso to overcome the limitations of manual project management systems and improve service to consumers.